Answer:

This is the Best answer for If y=xy+x^2+1, then when x=-1, dy/dx is?

y = -1y + (-1)^2 + 1

y = -y + 2

2y = 2

y = 1

d/dx(y) = d/dx(xy + x^2 + 1)

dy/dx = y + xdy/dx + 2x

dy/dx – xdy/dx = y + 2x

dy/dx(1 – x) = y + 2x

dy/dx = (y + 2x)/(1 – x)

dy/dx(-1,1) = (1 + 2(-1))/(1 – -1) = -1/2

If y=xy+x^2+1, then when x=-1, dy/dx is?

Solution : When , x= -1

y= -y+1+1 = -y+2

=> 2y=2

=>y=1

Now, dy/dx= d(1)/dx= 0

This is the correct answer for If y=xy+x^2+1, then when x=-1, dy/dx is?

in basic terms positioned x = tan ok. the place ok is a few consistent. Now resolve this given ingredient you will get to renowned that Y = ok. Calculate dy/dk and multiply it with dk/dx you will get dy/dx. and you will calculate dk/dx via calculating dx/dk and opposite it. wish it would help you. ðŸ™‚